(untitled) - Reischauer, August Kar (New York, 1917)
The present volume contains the seventh course of lectures offered by New York University upon the foundation known as the Charles F. Deems Lectureship of Philosophy. The University contracted April 15, 1895, with the American Institute of Christian Philosophy, a corporation chartered December 1, 1891, that the University would maintain said lectureship for at least twenty years by securing biennially a Lecturer, eminent in Science and Philosophy, who should treat in not less than six lectures some one of the most important questions of Science and Philosophy, with a special reference to its relation to the revealed truths of the Holy Scriptures and to the fundamental principles of Theistic Philosophy.
Keywords: Đạo Phật; Nhật Bản,Japan